"I Can’t Exercise Because My Foot Hurts Me Too Much." Does BMI Change after Common Foot and Ankle Surgeries? A Retrospective Review - Samantha N. Weiss MD; Margaret Higgins MD; Jonathan McKeeman MD; James R. Lachman MD (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: The World Health Organization reports that 1.9 billion people worldwide have a body mass index (BMI) that classifies them as being either overweight (BMI > 25) or obese (BMI > 30). Patients often claim, prior to orthopaedic surgery, that their physical activity and exercise is negatively impacted by their orthopaedic condition. Hip and Knee arthroplasty literature has established that patients with high preoperative BMI continue to have high BMI post-operatively, despite also reporting improvements in their joint pain. No such studies exist in foot and ankle surgery. The purpose of this study was to analyze changes in BMI after many common foot and ankle surgeries. Methods: A retrospective review of all patients undergoing bunion correction, flatfoot correction, 1st MTP arthrodesis, and midfoot arthrodesis procedures between November 2018 and December 2022 was conducted in this IRB approved, single center study. BMI data was collected from the electronic medical record for preoperative and 12 months postoperative time points. Descriptive statistics were reported for age, gender, diabetes, A1c for diabetic patients, smoking status, and overall follow up time. Repeated measures of analysis of variation were conducted with one between-groups factor being type of surgery. Results: 196 patients were included in the study. The average age was 62.1 years, 151(76.6%) patients were female. Average BMI amongst all patients preoperatively was 29.58 +/- 5.21, and postoperatively 29.79 +/- 5.33, with an overall average increase in BMI of 0.2182 +/- 2.21. Upon subgroup analysis, all surgical cohorts yielded an increase in postoperative BMI (bunion +0.2489 +/- 2.06, double arthrodesis +0.4767 +/- 1.37, 1st MTP fusion +0.2293 +/- 2.07, midfoot arthrodesis +0.0251 +/- 3.10) although these changes did not reach significance (p value 0.425). There was no significant difference observed in changes in BMI between surgical groups (p value 0.958). BMI outcomes were normally distributed with acceptable equality of error variances (Levene’s test p- values > 0.270). Conclusion: The current statistics surrounding the prevalence of overweight and obesity are staggering. The results of this study demonstrate that elective orthopaedic surgery of common foot and ankle procedures do not facilitate a change in BMI one year postoperatively, despite the goal of reducing chronic pain and increasing physical function, which is often cited as the primary restriction to exercise amongst patient populations. Additional studies are warranted to further elucidate changes in BMI to adequately council patients regarding postoperative expectations. Study Data Summary